1998
DOI: 10.1136/bjo.82.7.773
|View full text |Cite
|
Sign up to set email alerts
|

Development of a disease specific quality of life questionnaire for patients with Graves' ophthalmopathy: the GO-QOL

Abstract: Aim-To develop a reliable and valid disease specific quality of life questionnaire (the GO-QOL) for patients with Graves' ophthalmopathy (GO), that can be used to describe the health related quality of life and changes in health related quality of life over time as a consequence of disease and treatment. Methods-70 consecutive GO patients (age >18 years) who were referred for the first time to the combined outpatient clinic of the orbital centre and the department of endocrinology completed the 16 questions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
233
0
15

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(258 citation statements)
references
References 32 publications
10
233
0
15
Order By: Relevance
“…In this study, we found that GO-QOL scores of Korean patients were significantly correlated with disease severity and inflammatory activity measured by the modified NOSPECS score and CAS, respectively. In addition, as the Cronbach alphas of the Korean language survey used in this study were comparable with those of the Dutch GO-QOL survey (visual functioning, 0.86 in reference vs 0.90 in this study; and appearance, 0.82 in reference vs 0.88 in this study), 6 it is assumed that the validity and internal consistency of the Korean language questionnaire were also well preserved.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In this study, we found that GO-QOL scores of Korean patients were significantly correlated with disease severity and inflammatory activity measured by the modified NOSPECS score and CAS, respectively. In addition, as the Cronbach alphas of the Korean language survey used in this study were comparable with those of the Dutch GO-QOL survey (visual functioning, 0.86 in reference vs 0.90 in this study; and appearance, 0.82 in reference vs 0.88 in this study), 6 it is assumed that the validity and internal consistency of the Korean language questionnaire were also well preserved.…”
Section: Discussionmentioning
confidence: 74%
“…The consistency and reliability of the questionnaire were both well preserved, compared with Cronbach's alphas of the Dutch GO-QOL survey made by Terwee et al 6 The mean QOL score of visual function-associated questionnaire was 73.7±26 (mean±SD). The mean QOL score of appearance-related questionnaire was 61.9 ± 26.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate test-retest reliability of the FAQLQs, we used the intraclass correlation coefficient (ICC), using a one-way ANOVA [20,21,23]. Values should be above 0.70 for group comparison studies and above 0.90-0.95 for individual measurements over time [24].…”
Section: Discussionmentioning
confidence: 99%
“…The GOQOL consists of 16 items sub-divided into two scales: 'visual functioning' and 'appearance'. Subsequent studies comprising 70 -164 well-described patients have shown excellent reliability (25,44), supported its construct validity (25,44,45), and demonstrated good responsiveness (45). According to the developers, the GOQOL is available in six languages (46).…”
Section: Questionnaires For Patients With Thyroidassociated Ophthalmomentioning
confidence: 99%
“…The Graves' Ophthalmopathy Quality of Life Questionnaire (GOQOL) is a disease-specific HRQL instrument for patients with TAO (25,44,45). The development was based on a review of existing eye HRQL measures,…”
Section: Questionnaires For Patients With Thyroidassociated Ophthalmomentioning
confidence: 99%